6(5)-1=5(5-1)-3(7-2(1))

Simple and best practice solution for 6(5)-1=5(5-1)-3(7-2(1)) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(5)-1=5(5-1)-3(7-2(1)) equation:


Simplifying
6(5) + -1 = 5(5 + -1) + -3(7 + -2(1))

Multiply 6 * 5
30 + -1 = 5(5 + -1) + -3(7 + -2(1))

Combine like terms: 30 + -1 = 29
29 = 5(5 + -1) + -3(7 + -2(1))

Combine like terms: 5 + -1 = 4
29 = 5(4) + -3(7 + -2(1))

Multiply 5 * 4
29 = 20 + -3(7 + -2(1))

Multiply -2 * 1
29 = 20 + -3(7 + -2)

Combine like terms: 7 + -2 = 5
29 = 20 + -3(5)

Multiply -3 * 5
29 = 20 + -15

Combine like terms: 20 + -15 = 5
29 = 5

Solving
29 = 5

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5=q+2 | | 9(0)-7y=14 | | 10x-3=20+15 | | -8n+5(4n+8)=100 | | 2x-5x+3x-25+5x+45=180 | | -3p-6(5-2p)=4(p-2)-47 | | .1x+10=.35x | | -2=w^7 | | 5x+7=2.5(2x+2.8) | | 9x-7(0)=14 | | 6(5)=5(5-1)-3(7-2(1)) | | f-8=11 | | 8sin^2(30)=y | | 5n^2-22n+24=0 | | 11(x-6)=-5-6 | | 49m^2+12=56m | | -4(4k+6)=-3k+2 | | 9=X*36 | | 6x+3x=189 | | (7x-1)(7x+1)=1 | | 5-6p=49 | | 58+25= | | 5x-4=-4+6x | | 5+6p=49 | | 4(x-3)=18-6(4x+1) | | 1-6n+3=-46 | | 2x+(x+3)=75 | | 7p+26=-32p+-40+6p | | 5(2z+6)=-4(-5-2z)+3z | | z-3z=8z-7-z | | x=8pi-pi | | 5(x+2)=4x-8 |

Equations solver categories